2008
DOI: 10.1080/10641950701826554
|View full text |Cite
|
Sign up to set email alerts
|

β-Adrenoceptor Subtype Expression in Human Placenta and Umbilical Arteries in Normal and Preeclamptic Pregnancies

Abstract: Aberrations in the beta-adrenoceptor signalling systems, rather than in the regulation of expression of these receptors may occur in preeclampsia, as is the case in other hypertensive disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…However, the vascular responses during pregnancy may not be uniform and may vary depending on the vascular bed studied and the vessel size down the arterial tree, i.e., large, intermediate, small, and microvessels. The differences in the responses of various blood vessels can be related to differences in vasoconstrictor receptor distribution, receptor-coupling mechanisms, and postreceptor mechanisms particularly [Ca 2ϩ ] i control mechanisms and [Ca 2ϩ ] i sensitization path-ways (7,31,45). Previous studies (6) have shown that the mesenteric vascular resistance is elevated in rat models of HTN-Preg.…”
mentioning
confidence: 99%
“…However, the vascular responses during pregnancy may not be uniform and may vary depending on the vascular bed studied and the vessel size down the arterial tree, i.e., large, intermediate, small, and microvessels. The differences in the responses of various blood vessels can be related to differences in vasoconstrictor receptor distribution, receptor-coupling mechanisms, and postreceptor mechanisms particularly [Ca 2ϩ ] i control mechanisms and [Ca 2ϩ ] i sensitization path-ways (7,31,45). Previous studies (6) have shown that the mesenteric vascular resistance is elevated in rat models of HTN-Preg.…”
mentioning
confidence: 99%
“…In preeclampsia, a hypertensive gestational state, ß 2 -AR and ß 3 -AR protein levels in placentae were similar to those of normal patients, suggesting that aberrations in the ß-AR signaling, rather than in the regulation of ß-AR-subtype expression, may occur in preeclampsia [34]. This hypothesis is supported by the fact that fenoterol-and BRL37344-induced relaxations were partly reduced due to the attenuation of cAMP levels, suggesting that ß 2 -and ß 3 -AR agonists may have considerable future pharmaceutical implications in the clinical management of pregnancyrelated disorders (eg, preterm labor) or other conditions (eg, intrauterine growth restrictions) in which improvement in fetoplacental exchanges may be of interest [33].…”
Section: Hypertensionmentioning
confidence: 85%
“…Nevertheless, it is important to note that the authors used endotheliumdenuded artery rings, whereas many studies performed in human and animal models suggest a preferential endothelial location of ß 3 -AR. Finally, ß 3 -AR also was described in human hepatic artery [31], and its presence was confirmed in umbilical and placental arteries [34]. Surprisingly, although nebivolol has been described as a ß 3 -AR agonist in human [12] and rat vessels [5], a recent study reports that nebivolol was not a ß 3 -AR agonist in rat and human urinary bladders [35].…”
Section: ß 3 -Adrenoceptors In Blood Vesselsmentioning
confidence: 99%
“…The roles played by β3-AR in embryonic development and fetal life remain poorly understood. However, studies report β3-AR expression in human and animal germ cells, where it induces motility ( 81 ), in pre-implantation embryos ( 82 , 83 ), during the first stages of embryogenesis ( 84 ), in embryo tissues, and in placenta ( 85 , 86 ). Moreover, β3-AR is upregulated in the human pregnant myometrium where inhibits spontaneous contractions and represents the predominant subtype over β2-AR ( 87 , 88 ).…”
Section: Introductionmentioning
confidence: 99%